2022
DOI: 10.3389/fphar.2022.749312
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Safety of Advanced Intravitreal Therapeutic Agents for Noninfectious Uveitis: A Systematic Review and Network Meta-Analysis

Abstract: Background: To compare the efficacy and safety of advanced intravitreal therapeutic regimens, including a dexamethasone implant at 350 and 700 μg; a fluocinolone acetonide (FA) implant, 0.2 µg/day, 0.59 and 2.1 mg; intravitreal bevacizumab, 1.25 mg; intravitreal ranibizumab, 0.5 mg; intravitreal triamcinolone acetonide (IVTA), 2 and 4 mg; and standard of care (SOC, systemic therapy) for noninfectious uveitis.Methods: We searched the Cochrane Library database, EMBASE, Medline, clinicaltrials.gov until April 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… 13 Additionally, YUTIQ was ranked higher in probability of being the most efficacious drug for improving BCVA at 6 months over Ozurdex. 13 Unlike Ozurdex, the YUTIQ implant is made of an inert non-biodegradable material that does not require surgical removal. 5 , 7 Furthermore, the active compound FA in YUTIQ is more potent than dexamethasone, but is in a lower dose compared to its predecessor Retisert to minimize the side effects and is placed through a less invasive intravitreal injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 Additionally, YUTIQ was ranked higher in probability of being the most efficacious drug for improving BCVA at 6 months over Ozurdex. 13 Unlike Ozurdex, the YUTIQ implant is made of an inert non-biodegradable material that does not require surgical removal. 5 , 7 Furthermore, the active compound FA in YUTIQ is more potent than dexamethasone, but is in a lower dose compared to its predecessor Retisert to minimize the side effects and is placed through a less invasive intravitreal injection.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A recent systemic review and network meta-analysis comparing efficacy and safety of intravitreal therapeutic agents for NIU concluded that YUTIQ (FA implant 0.2 µg/day, calculated delivered dose) improved BCVA as much as Ozurdex (0.7 mg dexamethasone implant) at 6 months, but no 12 month data was provided for Ozurdex and this meta-analysis does not highlight the efficacy of YUTIQ over Ozurdex in patients refractory to topical corticosteroids and Ozurdex treatment. 13 Additionally, YUTIQ was ranked higher in probability of being the most efficacious drug for improving BCVA at 6 months over Ozurdex. 13 Unlike Ozurdex, the YUTIQ implant is made of an inert non-biodegradable material that does not require surgical removal.…”
Section: Discussionmentioning
confidence: 99%